Down's syndrome and acute lymphoblastic leukaemia: clinical features and response to treatment. Issue 4 (1st October 2001) - Chessells, J M; Harrison, G; Richards, S M; Bailey, C C; Hill, F G H; Gibson, B E; Hann, I M
Abstract : AIMS: To examine the clinical and biological features of acute lymphoblastic leukaemia in children with Down's syndrome (DS), to compare their survival with other children, and to determine if entry to trials and survival has improved. METHODS: Examination of presenting features and response to treatment in patients treated in two consecutive national trials, MRC UKALL X and XI. RESULTS: The proportion of children with DS was significantly higher in UKALL XI (1.9%) than UKALL X (0.9%). Children with DS tended to be under 10 years and to have the common ALL subtype. Cytogenetic analysis showed that favourable features, such as high hyperdiploidy and t(12;21) were less frequent but also that there was a lack of translocations associated with a poor prognosis. Children with DS showed no increase in risk of relapse at any site but their survival and event free survival were inferior to other children. These results were caused by an increased number of infective deaths during remission (11% compared to 2%). At five years overall survival was 73% in DS children compared with 82% in other children; event free survival was 53% compared to 63% in non-DS children. CONCLUSIONS: Entry of children with DS to national trials has increased and survival has improved. However they remain at risk of relapse and also of treatment related mortality. These findings emphasise the need for both intensive chemotherapy and optimal supportive care.